Rheumatoid arthritis susceptibility loci at chromosomes 10p15, 12q13 and 22q13. - Barton, A; Thomson, W; Ke, X; Eyre, S; Hinks, A; Bowes, J; Plant, D; Gibbons, L; Wilson, A; Bax, D; Morgan, A; Emery, P; et al. (2008)
The WTCCC study identified 49 SNPs putatively associated with rheumatoid arthritis at P = 1 x 10(-4) - 1 x 10(-5) (tier 3). Here we show that three of these SNPs, mapping to chromosome 10p15 (rs4750316), 12q13 (rs1678542) and 22q13 (rs3218253), are also associated (trend P = 4 x 10(-5), P = 4 x 10(-4) and P = 4 x 10(-4), respectively) in a validation study of 4,106 individuals with rheumatoid arthritis and an expanded reference group of 11,238 subjects, confirming them as true susceptibility loci in individuals of European ancestry.